Global software and IT : a guide to distributed development, rightshoring, and outsourcing - Ebert, Christof (Hoboken, N.J. : John Wiley & Sons, 2012)
'Global software engineering, implying both internal and outsourced development, is a fast-growing scenario within industry; the growth rates in some sectors are more than 20% per year. However, half of all offshoring activities are cancelled within the first 2 years, at tremendous unanticipated cost to the organization. This book will provide a more balanced framework for planning global development, covering topics such as managing people in distributed sites, managing a project across locations, mitigating the risk of offshoring, processes for global development, practical outsourcing guidelines, collaboration, and communication. Drawing on the author's vast experience, it shares best practices and survival strategies from projects of various types and sizes that involve different continents and diverse cultures'--
'This book will provide a more balanced framework for planning global development, covering topics such as managing people in distributed sites, managing a project across locations, mitigating the risk of offshoring, processes for global development, practical outsourcing guidelines, collaboration, and communication'--
Includes bibliographical references (p. 339-348) and index.
Keywords: Computer software -- Development; Project management; Computer software industry